THE EFFORTS OF TEACHERS OF GUIDANCE AND COUNSELING IN HELPING OVERCOME LEARNING DIFFICULTIES OF STUDENTS OF MAN 1 ACEH TENGGARA - Humaira Mustika (Al-Mursyid : Jurnal Ikatan Alumni Bimbingan dan Konseling Islam (IKABKI), 2021)
This research was conducted at MAN 1 Aceh Tenggara. The purpose of this study is to find out "The Efforts of Guidance and Counseling Teachers in Helping OvercomingLearning Difficulties for Students at MAN 1 Aceh Tenggara. The subjects of thisresearch are Guidance and Counseling teachers who have made various related effortsin helping to overcome students learning difficulties. This study uses a descriptivequalitative approach. The data collection technique in this study used direct observation / observation, interviews, and documentation of the Guidance and Counseling Teachers' Efforts in Helping Overcoming Student Difficulties in MAN 1 Aceh Tenggara. Data analysis uses three stages of the process, namely data reduction, data presentation, and drawing conclusions.Based on the research that has been done, the results show that: 1) the efforts ofthe guidance and counseling teachers in helping to overcome the learning difficulties of the students of MAN 1 Aceh Tenggara are quite good. 2) the form of learning difficulties  experienced by students in the field of English studies. 3) the factors that support and hinder the efforts of guidance and counseling teachers in helping to overcome student learning difficulties are the form of cooperation with homeroom teachers and subject teachers.Keywords : Counseling Teacher, Learning Difficulty